Environmental policing in the Tribal Trust Lands and African peasant responses in Zimbabwe, c.1960 – 2005 - Uledi, Peter (Stellenbosch : Stellenbosch University, 2024)
Thesis (DPhil)--Stellenbosch University, 2024.